Annual Plan 1994-95 Volume-IV VII. Transport, VIII. Communications, IX. Science, Technology & Environment, X. General Economic Services General Areas Government of Assam - Planning Commission (Planning Commission, 1994)
The Road communication system in Assam is grossly/in-adequate along with the other North Eastern States. In view of the added importance of Road Development in the North Eastern Region, a Working Group was set-up for preparation of a Master plan for perspective and Co-ordinated Road Development in the Region. The Master Plan has now been finalised and the objectives and Targets which are to be achieved within the next ten years i.e. upto 2001 A.D. are indicated below.
Planning and Development Department Government of Assam